Identifying the influence of winding angles on the strength properties of carbon fiber-reinforced plastic tubes - Meiirbekov, Mohammed; Yermekov, Abussaid; Nurguzhin, Marat; Kulbekov, Arman (Eastern-European Journal of Enterprise Technologies, 2025)
In this paper, a study of carbon fiber reinforced plastic tubes, which are widely used in overwhelming of technical industries, including aerospace industry, with single and combined winding angles (30°, 45°, 60° and 80°) fabricated by wet winding method on X-Winder machine has been carried out. The core problem addressed in this research is identifying optimal winding angles of carbon fiber reinforced plastic tubes at which the strength parameters remain in a relative equilibrium. Compressive strength, tensile strength and impact strength tests were carried out. The results of specimens with single winding angle showed that a maximum tensile strength of 630 MPa was achieved at a winding angle of ±30° and a maximum compressive strength of 380 MPa was achieved at an angle of ±80°. The maximum value of impact strength was achieved at a winding angle of ±60°. In order to obtain a balance in the strength characteristics of the tubular rods, combined reinforced winding with ±30°/45°, ±30°/60°, ±30°/80°, ±80°/45° and ±80°/60° angles were investigated. High values of compressive strength of 434 MPa, tensile strength of 675 MPa and impact strength of 165 kJ/m2 were achieved with ±30°/80° combined winding angle. The fibers of the material, which were oriented closer to the compression direction, resulted in reduced efficiency of transferring compressive forces between the fibers and decreased compressive strength. This uniform stress distribution permitted the load to be equally divided between the fibers, which effectively utilized their strength properties. Thus, results confirmed the importance of selecting the optimal winding angles to create carbon fiber reinforced plastic tubes with the required strength properties